Factors driving intention to use e-wallet services in Malaysia - Yapp, Emily Hon Tshin; Toh, Jia Qi; Lim, Xin Yee (Universal Publishers - Boca Raton, Florida, USA, 2022)
The purpose of this study is to determine the factors influencing technology users' intentions to adopt e-wallet services in Malaysia and utilized the Diffusion of Innovation Theory. A self-administered online questionnaire was used to gather data from 540 Malaysian respondents using a purposive sampling strategy. SPSS version 26 and SmartPLS 3.3.3 was used to analyse the data. Relative advantage and perceived security influence e-wallet adoption intention positively. While trialability and ubiquity have a positive effect on perceived security. It is also interesting to identify that Trialability has a medium effect on perceived security while relative advantage and perceived security have a small effect on usage intention. Ubiquity has a small effect on perceived security. Besides that, the Q-Predict values for usage intention were 0.493 and the PLS-predict demonstrated low predictive relevance. Research limitations/implications: The data was collected in June 2020. At that period of time, researchers did not expect that the adoption of e-wallet would have increase significantly due to the covid-19 pandemic. Practical implications: Organisations should pay attention particularly to trialability because this factor contributes the most towards the perceived security of e-wallet among Malaysian. As they are comfortable with e-wallet services and have confidence in its security, this will encourage adoption especially the late adopters. Besides that, e-wallet services providers should also stress the relative advantage of the usage of e-wallet, particularly in their marketing communication strategy. This research helps to understand what are the critical characteristics that are important for e-wallet adoption, particularly among the Malaysian, because previous research had identified that different countries would have different propensities to use the ewallet. Due to the differences, certain factors such as ease of use, relative advantage, visibility and perceived security need to be given consideration and attention in a country such as Malaysia. As a result, this study will revisit these factors whether these factors will contribute towards Malaysian intention to use e-wallet.